2018
DOI: 10.1101/332056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethylene signaling regulates natural variation in the abundance of antifungal acetylated diferuloylsucroses andFusarium graminearumresistance in maize seedling roots

Abstract: SummaryThe production and regulation of defensive specialized metabolites plays a central role in pathogen resistance in maize (Zea mays) and other plants. Therefore, identification of genes involved in plant specialized metabolism can contribute to improved disease resistance.We used comparative metabolomics to identify previously unknown antifungal metabolites in maize seedling roots, and investigated the genetic and physiological mechanisms underlying their natural variation using quantitative trait locus (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…The single transcriptomic analysis provides a landscape of defense response at a given time point (Ye et al, 2013); however, not all transcriptional changes observed are translated into proteins or metabolites. Therefore, combining transcriptomic data with those proteomic and metabolomic approaches can be used to comprehensively reveal the multilevel landscape of plant defense response and better understand the molecular mechanism of GSR resistance (Zhou et al, 2019;Sun et al, 2021). Recently, an integrative analysis combining transcriptomics and metabolomics showed that ZmHIR3 controls cell death at the later stage of GSR, probably through the transcriptional regulation of key genes and functional metabolites (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The single transcriptomic analysis provides a landscape of defense response at a given time point (Ye et al, 2013); however, not all transcriptional changes observed are translated into proteins or metabolites. Therefore, combining transcriptomic data with those proteomic and metabolomic approaches can be used to comprehensively reveal the multilevel landscape of plant defense response and better understand the molecular mechanism of GSR resistance (Zhou et al, 2019;Sun et al, 2021). Recently, an integrative analysis combining transcriptomics and metabolomics showed that ZmHIR3 controls cell death at the later stage of GSR, probably through the transcriptional regulation of key genes and functional metabolites (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%